(untitled) (Texas Journal of Philology, Culture and History, 2026)
The article analyzes the role of intelligent tutoring systems in transforming e-learning into a learner-centered and adaptive environment. The analysis showed that intelligent tutoring systems can transform e-learning from a simple content delivery system into an intelligent pedagogical environment operating on the basis of learner modeling, diagnosis, adaptive routing, rapid feedback, and individualized recommendations. At the same time, it was substantiated that the effectiveness of such systems depends not so much on the technology itself as on pedagogical design, data quality, the teacher’s role, ethical standards, and local content.